Pengaruh Ekstrak Daun Kepayang (Pangium edule Reinw.) sebagai Bahan Pestisida Nabati pada Mortalitas Ulat Grayak (Spodoptera litura F.) - Miaranty archi; Evi Mintowati Kuntorini; Rusmiati Rusmiati (Bioscientiae, 2020)
Grayak caterpillar is a pest that always attacks the crops of horticultural and vegetables in Indonesia every growing season that causes farmers to experience crop failure. Kepayang plants contains some secondary metabolite compounds including high glycocyanide acid in each part of the plant. The purpose of this study was to determine the effect and optimal dosage of kepayang leaf extract as a vegetable pesticide on grayak caterpillar mortality. This research used Non-Factorial Randomized Complete Random Design (RCRD) with four treatments in two observation times and each treatment there were three replications. The extraction was done by maceration method using aceton p.a and thickened using rotary evaporator. Mustard as grayak caterpillar feed is dipped in kepayang leaf extract with three dose levels of 1.5gr / L, 1.75gr / L, and 2gr / L is observed for 72 hours and 96 hours. The results showed that pepper leaf extract had an effect on mortality of grayak caterpillar. Variant dose of pepper leaf extract (1.5gr / L, 1.75gr / L, and 2gr / L) in this study have the same cidal effect on grayak caterpillar.